Entrepreneurship as a potential driving force for the further development of rural areas – good examples from Visegrad countries - Egedy, Tamás; Cerić, Denis; Konopski, Michał; Kučerová, Silvie Rita; Kulla, Marián; Nestorová-Dická, Janetta; Svobodová, Romana (IGiPZ PAN, 2015)
Entrepreneurial human capital and entrepreneurship are crucial elements for the further development of rural areas. In order to understand the role of rural enterprises it is essential to learn the characteristics of successful companies in local economies. The main aim of this paper is to demonstrate through the introduction of the activity, everyday practice and production procedure how non-agricultural and non-tourism enterprises can foster the development of rural and peripheral areas in the Visegrad countries. Nine local enterprises of different size, profile and development pathway were examined in order to highlight main experiences and lessons being vital for and adaptable in other disadvantaged areas. The results and company descriptions provided in the article are based on in-depth interviews, online data collection and statistical analyses.
24 cm
Keywords: rural entrepreneurship; rural economy; rural periphery; microenterprises and SMEs; local products